Ranking Hospitals Based on the Disasters Preparedness Using the TOPSIS Technique in Western Iran. Issue 1 (2nd January 2019) - Hosseini, Seyed Mojtaba; Bahadori, Mohammadkarim; Raadabadi, Mehdi; Ravangard, Ramin
Abstract: Background: Considering the uncontrollable occurrence of unexpected events and disasters around the world and Iran, paying attention to the readiness of hospitals, as the most important place to provide health care services, before occurring disasters is necessary and the identification of hospitals with low preparedness is very important. The present study aimed to rank hospitals based on the level of their preparedness for disasters using the TOPSIS technique. Materials and Methods: This was a cross-sectional and descriptive study conducted in the first half of 2018 to assess the preparedness of hospitals in Ahwaz for unexpected events. In this study, all hospitals affiliated to Ahwaz University of Medical Sciences (8 hospitals) were reviewed. The required data were collected using a standard questionnaire assessing the level of hospital preparedness in terms of structural preparedness (3 indicators), nonstructural preparedness (2 indicators), functional preparedness (13 indicators) and human resources (3 indicators) dimensions. The collected data were analyzed using the TOPSIS technique. Results: The results showed that the structural ( W = 0.4) and functional ( W = 0.1) preparedness dimensions had the highest and lowest weights, respectively. Also, Hospital D (CL = 0.778) and Hospital A (CL = 0.224) had, respectively, obtained the first and last ranks. Conclusion: Hospital managers need to get required information about disaster management and train their personnel in the emergencies and first aid by developing educational plans and ensure their active participation at the time of disasters through increasing their knowledge about and skills in different fields of work. In the case of structural and nonstructural preparedness, the hospital buildings should be retrofitted by the technical office of the university and the safe places considered for evacuations should be visited and evaluated every 6 months. It is also necessary to have all the hospitals equipped with the Emergency Operations Center (EOC) and to review its functions and activities regularly.